2009
DOI: 10.1080/07060660909507590
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of fusarium head blight of wheat withClonostachys roseastrain ACM941

Abstract: Fusarium head blight (FHB), caused by Gibberella zeae, is a devastating disease of wheat. A strain of Clonostachys rosea, ACM941 (American Type Culture Collection ATCC 74447), was evaluated for antibiosis against G. zeae in vitro and for control of FHB under greenhouse and field conditions in comparison to the registered fungicide Folicur (tebuconazole). Strain ACM941 reduced mycelial growth of the pathogen by 52.6% in dual-culture after 6 days and completely suppressed spore germination for 6 h when coculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…; Hue et al. ). Many others would be secondary invaders or participants in synergistic enhancement of pathogenicity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Hue et al. ). Many others would be secondary invaders or participants in synergistic enhancement of pathogenicity.…”
Section: Discussionmentioning
confidence: 98%
“…The fungi detected and quantified in each system were, where possible, classified as potential pathogens (Nguyen et al 1973;Hosford 1975;Desjardins et al 1993;Stiles and Murray 1996;Amarlou et al 2010;Bockus et al 2010) or potential antagonists of wheat pathogens (Mangan 1967;Fokkema and van der Meulen 1976;McGee et al 1991;Harman and Kubicek 1998;Xue 2002;Aggarwal et al 2004;Hue et al 2009). Many others would be secondary invaders or participants in synergistic enhancement of pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…nov. (Schroers, Samuels, Seifert, & Gams, 1999) is an ascomycete fungus that is reported to control diseases caused by a wide range of plant pathogenic fungi, including Alternaria spp. (Jensen, Knudsen, Madsen, & Jensen, 2004), Bipolaris sorokiniana (Jensen, Knudsen, & Jensen, 2002), Botrytis cinerea , Fusarium culmorum (Jensen, Knudsen, & Jensen, 2000), Fusarium graminearum (Xue et al, 2009) and Sclerotinia sclerotiorum (Rodriguez, Cabrera, Gozzo, Eberlin, & Godeas, 2011). Several biocontrol mechanisms are reported in C. rosea, including direct parasitism of pathogenic fungi (Li, Huang, Kokko, & Acharya, 2002;, antibiosis (Pachenari & Dix, 1980;Rodriguez et al, 2011), production of fungal cell wall degrading enzymes (Chatterton & Punja, 2009;Mamarabadi, Jensen, & Lubeck, 2008), induction of plant defence reactions (Lahlali & Peng, 2014;Roberti et al, 2008) and plant growth promotion (Roberti et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic and reproductive needs of the bacteria themselves slow down electron transfer and energy metabolism to achieve the inhibitory effect. 29 Hue et al 30 isolated a strain of Clonostachys rosea which was found to have a strong inhibitory effect on the growth and spore germination of F. graminearum. Our experimental results showed that S. cerevisiae Y-912 had a strong inhibitory effect on the growth of F. graminearum Fg1 and could control its germination rate and germ tube length.…”
Section: Discussionmentioning
confidence: 99%